2022
DOI: 10.3389/fpsyg.2022.805748
|View full text |Cite
|
Sign up to set email alerts
|

Parenting With a Kind Mind: Exploring Kindness as a Potentiator for Enhanced Brain Health

Abstract: A growing body of research has suggested that high levels of family functioning—often measured as positive parent–child communication and low levels of parental stress—are associated with stronger cognitive development, higher levels of school engagement, and more successful peer relations as youth age. The COVID-19 pandemic has brought tremendous disruption to various aspects of daily life, especially for parents of young children, ages 3–5, who face isolation, disconnection, and unprecedented changes to how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…One COVID-19 specific study found that teaching parents how to engage with their children through acts of kindness, developing trusting relationships, and responding with compassion increased parent-child resilience during the pandemic as measured by parental resilience and parent-reported child empathetic prosocial behavior levels (Johnson et al, 2022). Studies of children with neurodevelopmental disorders, such as autism spectrum disorder and intellectual disabilities, showed that positive parenting enhanced pandemic resilience, as measured by a family quality of life and parent-child relationship questionnaires (Bolbocean et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One COVID-19 specific study found that teaching parents how to engage with their children through acts of kindness, developing trusting relationships, and responding with compassion increased parent-child resilience during the pandemic as measured by parental resilience and parent-reported child empathetic prosocial behavior levels (Johnson et al, 2022). Studies of children with neurodevelopmental disorders, such as autism spectrum disorder and intellectual disabilities, showed that positive parenting enhanced pandemic resilience, as measured by a family quality of life and parent-child relationship questionnaires (Bolbocean et al, 2022).…”
Section: Introductionmentioning
confidence: 99%